Conception and fabrication of a new steerable microstrip antenna for ISM band applications - Al Gburi, Ahmed Jamal Abdullah; El Ansari, Abdelaaziz; Khandare, Shobhit; Allabouche, Kaoutar; Zakaria, Zahriladha (Electromagnetics Academy, 2025)
This paper presents the conception and fabrication of a new steerable microstrip antenna for ISM band applications. At first, the fundamental antenna element is designed, optimized, and miniaturized to operate at 2.45 GHz, exhibiting a narrow impedance bandwidth and a good gain. However, the standalone element lacks beam steering capability. To enable directional control of its radiation pattern, a novel 3 dB hybrid coupler is used to feed two identical optimized elements, forming a switched array antenna. The resulting configuration achieves a wide impedance bandwidth and improved gain with beam steering capability. The proposed steerable antenna is designed and fabricated on a Rogers RT/duroid 5880 substrate. The simulated results are validated with measured data, showing good agreement and confirming the design's performance.